WAYS TO INCREASE SUSTAINIBILITY OF THE TRANSPORTATION SYSTEM - Makarova, Irina; Shubenkova, Ksenia; Mavrin, Vadim; Boyko, Aleksey (Journal of Applied Engineering Science, 2017)
Ways to increase safety and sustainability of the city transportation system and, particularly, public transport development, transition to vehicles using alternative fuel as well as measures to promote cycling are considered in the article. This paper proposes the results of the new route network modeling and the concept of the smart-bike control system. The proposed smart-bike was developed to help untrained cyclist in the situations, when the values of his/ her physical condition as well as parameters of environment are critical. Prototype of the proposed system was tested in the laboratory environment.
Keywords: control system; smart-bike; alternative fuel; public transport; sustainability of transportation system